The Impact of RObotic Assisted Rehabilitation on Trunk Control in Patients with Severe Acquired Brain Injury (ROAR-sABI) - Letizia Castelli; Claudia Loreti; Anna Maria Malizia; Chiara Iacovelli; Sabina Renzi; Luca Fioravanti; Vincenza Amoruso; Ilaria Paolasso; Francesca Di Caro; Luca Padua; Silvia Giovannini (Applied Sciences)
Daily activities require balance and control posture. A severe Acquired Brain Injury (sABI) disrupts movement organization, control and execution, affecting trunk control and balance. Trunk control therapy for difficult patients requires known and novel methods. This study analyzes how hunova® robotic platform therapy affects sABI patients’ sitting balance and trunk control. Twenty-six sABI patients were randomized into the experimental group (HuG) that employed hunova® for trunk control in addition to traditional therapy and the control group (CoG) that received only conventional rehabilitation. Clinical assessments were performed for trunk, balance, cognitive and motor performance, disability, autonomy, quality of life, and fatigue. Both static and dynamic sitting balance and trunk control were assessed with hunova®. HuG and CoG were significant in intragroup analysis. Intergroup comparisons showed substantial differences in trunk control, affected side motor function, autonomy, quality of life, and fatigue. Only patients with HuG improved statistically in the instrumental assessment of trunk control and sitting balance. Between-group analysis showed that a statistically significant difference emerged in COP path and trunk movement. The study found effectiveness and adaptability of hunova® for trunk control rehabilitation, showing improvement in static and dynamic trunk control, motor function, autonomy, quality of life and fatigue in sABI patients. Registration: NCT05280587.